Synthesis of Electron-Deficient N1-(Hetero)aryl 3,3,5,5-Tetramethyl Piperazinones - Alanine, Thomas A.; Stokes, Stephen; Scott, James S. (Synlett, 2017)
An alternative synthesis of N1-(hetero)aryl 3,3,5,5-tetrasubstituted piperazin-2-ones is demonstrated using a copper-mediated Goldberg arylation of a common intermediate in good to fair yields. An improved synthesis of 3,3,5,5-tetramethyl piperazin-2-one is also described. This method allows for the synthesis of substituted piperazin-2-ones which are challenging or inaccessible using traditional Bargellini chemistry.
Keywords: piperazin-2-ones; Bargellini; copper; Goldberg; hindered amines